DISKURSUS ILMU PENDIDIKAN ISLAM PADA PERIODE TABI’IN - Moh. Sholihuddin (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2021)
The evolutionary process that occurred from the khulafahurrasydin period was then taken over by the tabi'in. then the emergence of generations in the field of science in accordance with their expertise. Education that occurred in the tabi'in era underwent very significant changes. Referring to the field of science in accordance with the subject matter of each field of the tabi'in who learned and studied a lot by friends. Initiating very broad knowledge with various descriptions of subject matter to be taught to students and the next generation, subject matter taught to students includes religious knowledge such as the Qur'an, Hadith, Fiqh, Tafsir, Morals, Arabic and general sciences such as History , Literature, Arts and Natural Sciences. Thus the development of science is increasingly rapid until the times